Topography of Dopamine Transporter Availability in the Cerebellar Variant of Multiple System Atrophy. Issue 3 (2nd November 2016) - Nocker, Michael; Seppi, Klaus; Boesch, Sylvia; Donnemiller, Eveline; Virgolini, Irene; Wenning, Gregor K.; Poewe, Werner; Scherfler, Christoph
Abstract: Background: Voxel‐wise comparison of [ 123 I]‐2β‐carbomethoxy‐3beta‐(4‐iodophenyl)tropane ([ 123 I]β‐CIT) radioligand distribution measured by single‐photon emission computed tomography (SPECT) revealed distinct patterns of reduced dopamine transporter (DAT) availability in the Parkinson's variant of MSA (MSA‐P). The aim of this study was to identify the monoamine transporter distribution pattern in patients with the cerebellar variant of MSA (MSA‐C). Additionally, monoamine transporter availability was investigated in a small cohort of patients with sporadic adult‐onset ataxia (SAOA). Methods: [ 123 I]β‐CIT SPECT was performed in patients with MSA‐C (n = 12), MSA‐P (n = 14), SAOA (n = 5), and controls (n = 15) matched for age. Parametric images of [ 123 I]β‐CIT binding potential (BPND ) were generated and analyzed by statistical parametric mapping (SPM) and region of interest (ROI) analysis. Results: SPM localized significant reductions of [ 123 I]β‐CIT BPND in the striatum, midbrain, and pons in MSA‐C compared to controls. When compared with MSA‐P, the striatal DAT decline was significantly less affected in MSA‐C. ROI analysis revealed reductions of striatal and midbrain [ 123 I]β‐CIT binding in MSA‐C compared to SAOA, whereas no significant difference was apparent between the SAOA and control groups. Conclusions: Midbrain and pontine monoaminergic transporter binding was severely impaired in MSA‐C, matching the underlying pathological features. Striatal DAT availability was relatively less affected in MSA‐C compared to MSA‐P, reflecting measureable, but less‐profound, degeneration of the nigrostriatal dopaminergic projections. Preliminary results of reduced striatal and midbrain [ 123 I]β‐CIT binding in MSA‐C, compared to SAOA, suggest that the potential of DAT‐SPECT as a surrogate marker in the diagnostic workup of patients with adult‐onset cerebellar ataxia should be further investigated.